Essence and contents of the notion "safety" in context of the Ukraine national safety ensuring in border sphere. - Kashtelian, S. О. (Honor and Law, 2019)
Essence and contents of the notion "safety" in context of the Ukraine national safety ensuring in border sphere are generalized. Main objective features of the notion to safety are determined. Objects and subjects to national safety are presented in generalized type. The collection action of safety ensuring is generalized.